Untersuchung retrosternaler Lymphknotenmetastasen beim Mammakarzinom: Lymphszintigraphie und Kernspintomographie - Linden, A.; Reusch, Karola; Smolarz, Kamilla; Jungehülsing, M.; Theissen, P.; Bolte, A.; Schicha, H. (Nuklearmedizin - NuclearMedicine, 1991)
In 21 patients with breast cancer (pT1–4, N0, M0) internal mammary lymphoscintigraphy and magnetic resonance imaging (MRI) were performed to evaluate retrosternal lymph node metastases. In 6 patients normal findings of lymphoscintigraphy were confirmed by MRI. In the 15 patients with focal defects seen by lymphoscintigraphy no lymph nodes were found by MRI in 5 in the corresponding area, 5 showed normal-sized lymph nodes (<1 cm) and 5 enlarged lymph nodes indicating metastatic infiltration. In addition to internal mammary lymphoscintigraphy MRI may offer the possibility to improve TNM staging in patients with breast cancer.